A school curriculum for Fetal Alcohol Spectrum Disorder: advice from a young adult with FASD. Issue 2 (1st February 2017) - Brenna, Beverley; Burles, Meridith; Holtslander, Lorraine; Bocking, Sarah
ABSTRACT: While a significant number of individuals in Canada and globally are affected by prenatal fetal alcohol exposure, scant research exists that focuses specifically on the subjective experiences of this population. Based on a single case study exploring through Photovoice methodology the life experiences of a young adult with Fetal Alcohol Spectrum Disorder (FASD), this research paper utilises Schwab's curriculum commonplaces as a framework to present results pertinent to the field of Education. Four themes emerged that illuminate the participants' resilience and self-awareness of issues related to independence versus support, strengths and challenges, attitude and adaptation strategies, and advice for others. Curriculum suggestions based on the findings are offered for educators working with young people with FASD in general education settings. Further implications for Education and suggestions for additional research are included.